KEWENANGAN KURATOR DALAM PEMBERESAN BOEDEL PAILIT DEBITUR YANG MASIH DALAM SENGKETA - Rokhma, Fadila Ilaina; Warka, Made (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
This research investigates the role and authority of curators in handling disputes related to the settlement of debtors' bankruptcy cases, with a focus on the impact of unclear time limits in the bankruptcy context. The analysis involves exploring the bankruptcy criteria, the authority of the curator, and the challenges arising from disputes in the resolution process. In addition, this research discusses the impact of unclear time limits on efficiency, fairness, reputation and trust in the bankruptcy legal system. The findings show that the role of the curator has crucial relevance in maintaining a balance of interests and ensuring a fair settlement. However, unclear time limits can cause extra stress on courts, slow down the process and impact stakeholder confidence. Suggestions involve setting clear time limits, adjustments based on case complexity, and increasing the openness of the legal system. This research provides in-depth insight into the complexities of bankruptcy, the role of the curator, and the impact of uncertainty over timing. Implementation of these suggestions is expected to improve the integrity and effectiveness of the bankruptcy legal system